2023
DOI: 10.13057/biodiv/d231229
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of arbuscular mycorrhizal fungi in asphalt post-mining land in Buton Island, Indonesia

Abstract: Abstract. Tuheteru FD, Husna, Albasri, Effendy HM, Arif A, Basrudin, Tuheteru EJ, Mulyono S, Irianto RSB. 2022. Diversity of arbuscular mycorrhizal fungi in asphalt post-mining land in Buton Island, Indonesia. Biodiversitas 23: 6327-6334. Studies on the presence and diversity of Arbuscular Mycorrhizal Fungi (AMF) on overburden (OB) and asphalt post-mining areas in Buton Island are still limited. The purpose of this study was to examine the presence and diversity of AMF on OB and asphalt post-mining stockpiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Results of this study showed that the dominant AMF family was Glomeraceae at a percentage of 70%. Several studies also showed the same results, in which Glomeraceae was dominant in the post-mining area of nickel (Prayudyaningsih et al, 2019), coal (Ezeokoli et al, 2020), asphalt (Tuheteru et al, 2022), gold (Tuheteru et al, 2020), and limestone (Suting and Devi, 2021). Glomeracecae was reported to be dominant in the rhizosphere of several tropical tree species .…”
Section: Total Amf Types In Field and Trap Culturementioning
confidence: 56%
See 1 more Smart Citation
“…Results of this study showed that the dominant AMF family was Glomeraceae at a percentage of 70%. Several studies also showed the same results, in which Glomeraceae was dominant in the post-mining area of nickel (Prayudyaningsih et al, 2019), coal (Ezeokoli et al, 2020), asphalt (Tuheteru et al, 2022), gold (Tuheteru et al, 2020), and limestone (Suting and Devi, 2021). Glomeracecae was reported to be dominant in the rhizosphere of several tropical tree species .…”
Section: Total Amf Types In Field and Trap Culturementioning
confidence: 56%
“…AMF served as a tool for restoring the degraded land and the disturbed ecosystem (Asmelash et al, 2016), and for the post-mining land (de Moura et al, 2022) in particular. Several studies showed that AMF was capable of accelerating the succession of natural vegetation in several post-mining land conditions worldwide, including coal (Husin et al, 2017), gold (Tuheteru et al, 2020), and asphalt (Tuheteru et al, 2022). According to previous reports, AMF could improve the growth of tropical tree species in soil media from a post-gold mining land at a nursery and field scale in Bombana (Arif et al, 2021;Husna et al, 2021a).…”
Section: Restoration Of Soil/landmentioning
confidence: 99%
“…Havil) (Cahyono et al, 2015). Samama wood belongs to strong class II-III and durability class IV (Halawane, 2015;Tuheteru et al, 2019). This means that Samama wood has low durability and needs protection or preservation against biodeterioration agents.…”
Section: Introductionmentioning
confidence: 99%